Pembuatan Video Profile Lulusan Program Sarjana Sistem Informasi Peminatan DKV - Deli Deli; Hendy Hendy (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The growth speed of technology developments are encouraging information system to develop significantly. One of the example were making videos that can renew a company identity as a form of promotion and visualization needs of a company profile. This article describes the implementation of Job Training (KP) to an agency in the city of Batam, namely Batam International University, namely the Undergraduate Program in Information Systems. Practical work projects were carried out because of the need to renew the form of promotion of the Information Systems Undergraduate Program in the form of introducing graduate profiles. So the authors decided to work together by making a video profile of an information system graduate specializing in DKV. The author will use the Transition technique during the design of the video profile. The output in the form of a video will be distributed via Youtube social media.